2021
DOI: 10.1002/gps.5486
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and effectiveness of psychological interventions on co‐occurring mood and anxiety disorders in older adults: A systematic review and meta‐analysis

Abstract: Objectives Co‐occurring mood and anxiety disorders are common in older adult populations and are associated with worse long‐term outcomes and poorer treatment response than either disorder alone. This systematic review and meta‐analysis aimed to examine the efficacy and effectiveness of psychological interventions for treating co‐occurring mood and anxiety disorders in older adults. Method The study was registered (PROSPERO CRD4201603834), databases systematically searched (MEDLINE, PSYCINFO, PubMed and Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…These clinical outcomes were consistent with a prior study of predominantly younger adults using the same telemedicine platform ( 28 ). Large effect sizes found in the current study compare favorably to the small to medium effect sizes found in meta-analyses of app-supported DMHIs compared ( 23 ), andat least comparable to or larger than the medium to large effect sizes for depression and anxiety found in traditional in-person psychotherapy studies of both younger and older adults ( 39 43 ). Future research is needed to confirm these observations on effect sizes via different psychotherapy modalities.…”
Section: Discussionsupporting
confidence: 74%
“…These clinical outcomes were consistent with a prior study of predominantly younger adults using the same telemedicine platform ( 28 ). Large effect sizes found in the current study compare favorably to the small to medium effect sizes found in meta-analyses of app-supported DMHIs compared ( 23 ), andat least comparable to or larger than the medium to large effect sizes for depression and anxiety found in traditional in-person psychotherapy studies of both younger and older adults ( 39 43 ). Future research is needed to confirm these observations on effect sizes via different psychotherapy modalities.…”
Section: Discussionsupporting
confidence: 74%
“…Subsequent moderation analyses will enable understanding of factors that might be associated with better treatment success such as baseline severity, disorder type, age, gender and personality factors. Further, the use of a long-term (12 month follow up) period as the primary outcome eliminates the common problem in clinical trials in this population which have shorter follow up periods [70] and enables a thorough cost analysis of outcomes. Therefore, the results of this study could improve access to mental health services for older adults, as well as informing the translation of evidence-based stepped care models of psychological interventions for anxiety and depression into the older adult mental health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that training aspects of attention can relieve anxiety (e.g., yoga, meditation) (Kiken et al 2015;Shreve et al 2020;Simon et al 2020;Wuthrich et al 2021). Besides, inattention is one of the clinical manifestations of anxiety (Blaskovits et al 2017).…”
Section: Introductionmentioning
confidence: 99%